2012
DOI: 10.1021/cg300483c
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Thiacalix[4]arene-Supported Nickel(II)/Cobalt(II) Complexes Sustained by in Situ Generated 5-Methyltetrazolate Ligand

Abstract: Solvothermal reactions of thiacalix[4]arene, NaN 3 , and acetonitrile in the presence of nickel(II)/cobalt(II) salts yielded four discrete complexes sustained by the in situ generated 5-methyltetrazolate ligand, [Ni II 12 (PTC4A) 3 (μ 6 -CO 3 ) 2 (μ-Mtta) 2 (μ-Mtta) 4 (μ 4 -Mtta) 2 (Py) 4 ]·7DMF·2Py·dma (1), [Co II 12 (PTC4A) arene; H 4 BTC4A = p-tert-butylthiacalix[4]arene; HMtta = 5-methyl tetrazolate). Crystal structural analyses revealed that complexes 1−3 are stacked by pseudotrigonal planar entities, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…[38][39][40][41][42][43][44][45][46] In lesser occasions, the incorporated CO 3 2À moieties may be rather considered as being encapsulated inside the coordination cage. [47][48][49][50][51] In any case, two carbonate anions have never been forced to lie so close to each other as within complex 2. To the best of our knowledge, the closest intermolecular contact between CO 3 2À species observed to date (2.487 Å) was found within the compound [Y(H 2 O)] 2 (C 2 O 4 )(CO 3 ) 2 , from a structure resolved by powder diffraction methods.…”
Section: Description Of Structuresmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46] In lesser occasions, the incorporated CO 3 2À moieties may be rather considered as being encapsulated inside the coordination cage. [47][48][49][50][51] In any case, two carbonate anions have never been forced to lie so close to each other as within complex 2. To the best of our knowledge, the closest intermolecular contact between CO 3 2À species observed to date (2.487 Å) was found within the compound [Y(H 2 O)] 2 (C 2 O 4 )(CO 3 ) 2 , from a structure resolved by powder diffraction methods.…”
Section: Description Of Structuresmentioning
confidence: 99%
“…In this aspect, the tetrasulfonylcalix [4]arene 3-4H [18,19], as shown in Figure 1, represents a very suitable polydentate ligand offering four phenolate groups together with four sulfonyl moieties as coordinating sites, to form metallomacrocycles as well as supramolecular capsules or cages when interacting with metallic cations [20]. The formation of supramolecular coordination compounds of highly nuclearities, based on its parent compound 4-4H has been recently documented [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Liao et al . utilized 120° 1,3‐H 2 BDC and 5‐sulfoisophthalic acid (5‐S‐1,3‐BDC) as linkers, two open wheel‐like square structure was obtained rather than octahedral cage [43,52] . They also found that decreasing the ratio of 5‐S‐1,3‐BDC to the Co 4 (calix) PSBU, an unprecedented tetrahedral MCCC‐84 was formed due to the sulfonic groups also participated in coordination [43] .…”
Section: Structure Of Molecular Cages With Metal Cluster Nodesmentioning
confidence: 99%